UJI AKTIVITAS EKSTRAK DAUN MBOA (Melastomata malabatricum) TERHADAP HAMA GUDANG Callosobruchus sp (COLEOPTERA:BRUCHIDAE) PADA KACANG HIJAU (Phaseolus radiata L.) - Hartini Haris; Yustina Maria Silvia Wonga Puu (Agriculture Faculty of Flores University, 2010)
Activity Test Extract Mboa Leaf (Melastomata Malabatrikum) against warehouse pest Callosobruchus Sp (Coleoptera : Bruchidae) Green bean (Phaseolus Radiata L.). Green beans are an important crop in the tropics and have long cultivated in Indonesia. Green bean production in quantity and quality is strongly influenced by the presence of pest and diseases. The damage caused by insects ensued can reach 70% (Kartasapoetra, 1987). Given the magnitude percentage damage inflicted by insects CallosobbrushusSp is a necessary control measure. This study aims to determine the activity of leaf extract Mboa (M. Mallabatricum) against warehouse pest Callosobruchus Sp. This study uses a CDR with four treatments (M25, M50, M75, M100) and repeated 10 times. The result showed extra activity Mboa leaves (M. Mallabatricum) against Callosobruchus Sp to test a contact poison can cause Callosobruchus Sp morality above 80% seen in the treatment of M50, M75, and M100 of 9.987%. repellant test showed a decrease traffic to continue successive treatment – participated in treatments M25 (61%), M50 (46%), M75 (43%), M100(34%) and mortality due to neurological disorders for M25 (7.34%), M50 (7.99%), M75 (8.54%), and M100 (9.21%). An antibody test can suppress high levels of oviposition in each treatment. M25 (31.21%), M50 (71.01%), M75(79.5%), and M100 (87.22%).